The effect of empowerment program based on the social cognitive theory on the activity of daily living in patients with chronic obstructive pulmonary disease - Fatemeh Aliakbari; Forouzan Mohammad Alipour; Elahe Tavassoli; Morteza Sedehi (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE AND AIM: Chronic obstructive pulmonary disease (COPD) is one of the most common chronic diseases. The patient's fear and anxiety of shortness of breath and coughing during exercise may lead to a decrease in patients' daily activities. Therefore, the present study aimed to determine the effect of empowerment program based on the social cognitive theory (SCT) on the daily activity of patients with COPD. METHODS: This quasi-experimental study was performed on 70 patients with COPD referred to Kashani and Hajar centers in 2019. Samples were randomly divided into two groups of experimental and control. Data collection tools included demographic information questionnaire and activity of daily living questionnaire, specific for COPD, and a researcher-made questionnaire for measuring SCT constructs. For the experimental group, the training program consisted of four theoretical and practical sessions of 40 min/week. The data were collected at three time points, before, immediately and 3 months after the training are 3 time. The data were analyzed by SPSS software using descriptive and inferential statistics. RESULTS: The difference between the mean scores of behavioral ability, self-efficacy, and empowerment in the three stages was significant only in the experimental group (P < 0.001). The mean daily activity score of patients before, immediately, and 3 months after intervention showed a statistically significant difference between the two groups (52.46 ± 21.98, 63.36 ± 21.95, and 71.34 ± 19.02), respectively, in the intervention group, and (51.79 ± 19.29, 53.70 ± 19.28, and 53.82 ± 19.26), respectively, in the control group (P < 0.001). CONCLUSION: The results of this study showed that empowerment of patients through interventions based on SCT can increase the daily activity of patients with COPD. Because nurses play an important role in patient education and improvement, it is hoped that the findings of this study will be used as a strategy to increase the daily activity and ultimately improve the quality of life in these patients.